Attitude determination and control of LEO microsatellites - Wee, Melisa Toon Cheng. (2008)
The Attitude Determination and Control System algorithm and code have been developed and tested for the possible use in the proposed X-Sat, a LEO microsatellite of NTU. The X-Sat is currently under development and is expected to be launched in 2005 into a circular orbit at a height of 800km. An Equatorial orbit is preferred, though varying inclined orbits have been examined in this research. A combination of a 3-axis magnetometer, a Sun sensor and two Earth Horizon sensors are used for attitude determination. As for the actuators, magnetic torquers and reaction wheels are used during different operational phases. Exploration on the ability of fine pointing and large angular slew manoeuvre using the reaction wheel controller is one major thrust in this project. This is particularly so as imaging is likely to be one of the main objectives of X-Sat. The effect of different perturbation torques on the proposed satellite are studied. The simulation results show good convergence in attitude to about 5° pointing accuracy when using magnetometer measurements and 0.2° for Sun and Earth Horizon measurements. Finally, embedding the software onto a digital signal processor (DSP), TMS320C31, is considered. This provides a better understanding of the real-time dynamics and would lead to the development of the ADCS onboard X-Sat.